Relationship between postoperative nodal skip metastasis of mid-thoracic esophageal squamous cell carcinoma and patient prognosis and its value in guiding postoperative adjuvant treatment - Gao, Hong-Mei; Zhao, Xiao-Han; Shen, Wen-Bin; Li, You-Mei; Li, Shu-Guang; Zhu, Shu-Chai (Frontiers in Surgery, 2023)
Objective To evaluate the predictive role of nodal skip metastasis (NSM) in the prognosis of lymph node-positive mid-thoracic esophageal squamous cell carcinoma, and to evaluate the significance of postoperative adjuvant treatment in patients with different sites of metastatic nodes. Methods A retrospective analysis was performed on clinical data of 321 lymph node-positive mid-thoracic esophageal squamous cell carcinoma patients who underwent surgery in the Fourth Hospital of Hebei Medical University. Based on the site and condition of lymph node metastasis by postoperative pathology, the patients were divided into two groups: NSM group and non-NSM (NNSM) group. The propensity score matching (PSM) method was employed to match the two groups. The prognostic factors of patients before and after PSM as well as the effect of different adjuvant treatment modes on the prognosis of patients before and after PSM were analyzed. SPSS 29.0 statistical software was used for analysis. Results PSM in a 1 : 1 matching ratio was performed, 103 patients were assigned to NSM group and NNSM group respectively. Significant differences were found in the 3- and 5-year OS and DFS between the two groups before PSM, the 3- and 5-year OS also showed a significant difference after PSM (P < 0.05). Multivariate analysis illustrated that gender, postoperative adjuvant treatment mode, N stage and lymph node metastasis were independent risk factors for OS and DFS after PSM (P < 0.05); for NSM patients, postoperative adjuvant chemotherapy and radiotherapy significantly prolonged OS and DFS before and after PSM (P < 0.05). But no significant difference was found in OS and DFS for NNSM patients after PSM (P > 0.05). Conclusion Postoperative NSM is a good prognostic factor for patients with mid-thoracic esophageal squamous cell carcinoma, postoperative adjuvant chemoradiotherapy was recommended for those group, thereby gaining survival benefits.